Estimation of filament temperature and adhesion development in fused deposition techniques - Costa, S. F. (2017)
This work presents an analytical solution to the transient heat conduction developing during filament deposition in Fused Deposition Techniques (FDT), which is coupled to a routine that activates or deactivates all relevant local boundary conditions depending on part geometry, operating conditions and deposition strategy. Boundary conditions include contact between filament segments, between filament segments and the support, as well as heat transfer with the environment. The resulting MatLab code comprises an adhesion criterion that is used to estimate whether contiguous filament segments will adhere adequately to each other prior to solidification. Predicted and experimental data for the filament surface temperature showed very good agreement. Also, adhesion predictions were in accordance with the results of real peel-like tests. The practical potential of this calculation tool is demonstrated by an application example.